ORGANISATIONAL RESTRUCTURING AND TURNOVER INTENTION AMONG BANK EMPLOYEES IN NIGERIA (2014)
Studies on organisations have focused on restructuring as strategic response to increased competitive pressure of globalization and the need to be more efficient. The effectiveness of restructuring depends on the influence of work attitude and behaviour (Job Satisfaction (JS), Organisational Commitment (OC) and Turnover Intention (TI)) of surviving employees which had been inadequately studied in Nigeria’s banking sector. This study was conducted to examine organisational restructuring and labour turnover intention in selected banks in Nigeria. Survey design was adopted and a synthesis of organisational change and planned behaviour theories provided the conceptual framework. Three banks were purposively selected. The banks were United Bank for Africa (UBA) (which change her management and promotion structure, software and operational system after merger), Unity Bank (UB) (which downsized after merger of nine banks), and Mainstreet Bank Plc (MB) (which laid off staff after acquisition of two other banks). A structured questionnaire was used to obtain data on socio-demographic characteristics, perception on restructuring, JS, OC and TI and administered to 400 respondents. Cochran’s sample size was used to select respondents across branches of the banks in Ibadan on the basis of proportionate random sampling technique (UBA 280, UB 55, MB 65). The levels of JS, OC and TI each were measured with 5-point Likert scale with 20-item categorized as low (≤33), moderate (34-66) and high (> 66). Twenty-one in-depth interviews (IDI) were conducted among the staff in each of the banks across cadres (management, senior and junior).Quantitative data were analysed using descriptive statistics and Chi-square test at p≤ 0.05, while qualitative data were content analysed. Respondents’ age was 34.7±6.2 years. 51.0% are males, 50.3% are single, 85.1% had tertiary education, 51.0% earned N35, 000 and above monthly. Also, 52.4% of the respondents from UBA, 58.3% (UB) and 61.6% (MB) perceived restructuring as good. Respondents (76.5% in UBA< 72.7% in UB and 55.4% in MB) agreed that restructuring positively affected technology, status, workload, income and morale. Respondents from UBA (52.4%), UB (58.7%) and MB (58.3%) who perceived restructuring as good had low, moderate and low TI respectively. Respondents in UBA (51.5%), UB (87.5%) and MB (92.9%0 with high JS had high OC. Respondents in UBA (19.6%), UB (36.7%) and MB (71.4%) with high OC had low TI. Respondents in UBA (17.6%), UB (43.8%) and MB (64.3%) with high Js had low TI. Age (X 2 =23.38), sex (X 2 =29.00), educational level (X 2 =25.67), marital status (X 2 =28.09), working experience (X 2 =132.12), and bank (X 2 =32.97) were all positively associated with TI. Findings from the IDI supported employees’ perception that restructuring influence intention to leave irrespective of cadre. Employees’ perception of organisational restructuring positively influenced commitment, job satisfaction and turnover intention. Management of banks should provide adequate support system to reduce employees’ turnover intention as banking sector continues to undergo restructuring.